PEMANFAATAN EKSTRAK HERBAL TERHADAP PRODUKTIVITAS DAN MUTU AYAM PEDAGING SEBAGAI UPAYA KETAHANAN PANGAN DI KALIMANTAN TIMUR BERBASIS PETERNAKAN RAMAH LINGKUNGAN - Supomo Supomo; Eka Siswanto; Ine Ventyrina (Jurnal Ilmiah Manuntung, 2016)
Quality broilers become a serious problem for farmers. Many studies done to solve these problems, one of them by making use of natural materials. Some plants are known to have the ability to improve the quality of broilers as bitter, ginger and onions tiwai. This study aimed to determine the effect of ethanol extract of the herb on the quality of broilers. Subjects used is Strain Cobb broiler DOC. A total of 60 chickens were kept in a cage stage measuring 1.5 x 1.5 m for 30 days. Subjects were divided into five treatment where each treatment consisted of four tails. The experiment was conducted with three replications using a completely randomized design. Such treatment includes control (P0), the ethanol extract of sambiloto 0.02 % (P1), the ethanol extract of umbi bawang dayak 0.05 % (P2), the ethanol extract of temulawak 0,075 (P3), Product Imugas (P4). Quality parameters include coarse fat content and crude protein. The data obtained were statistically analyzed using analysis of variance (ANOVA). The results showed that the treatment of all types of ethanol extract of the herb can improve the quality of broilers compared to control (sig < 0.05), the type of treatment is best to P4. Quality parameters which include : crude protein and crude lipid. Levels of the protein, which is the highest in treatment P4 by 23.87% . Fat content, which is the lowest in treatment P4 of 10.50%